NARKOBA DAN HUKUMAN MATI AKIBAT KORBAN PERDAGANGAN PEREMPUAN - Moh. Rosyid (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2015)
Narcotics are substances causing change of consciousness. Psychotropic is a substance that causes changes in mental activity and behaviour. There is negative impacts on its users. Surprisingly, the demand for narcotics is increasing. Some starts it as trial and error, to have fun, be used under certain conditions such as sadness, tense and disappointed, abuse / deviation and addicts. With the increasing demand, drug sellers attempt to increase their market in various ways including using women as couriers, although the death penalty confronting. The issue needs to be discussed further is the reasons these women becoming drug couriers. Data shows some women are trapped by drug sellers and they are victims of human trafficking promised to be married.Poverty is one factor of this problem. Thus, among the solutions is to fight against poverty by means of entrepreneurship education facilitated by government to become independent generation. Poverty is one of casualties in war against drug. Parents awareness to monitor and educate their children needs to be strengthen in order to prevent becoming targets of drugs' mafia, both becoming user or dealers.